DEKONSTRUKSI HUSEN MUHAHAMMAD TEHADAP KONSEPSI KEPEMIMPINAN WANITA - M. Toha, Fahmi Rusdi (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
The results showed that according to Hussein Muhammad, women can become leaders based on considerations of benefit not for gender reasons. The success and failure of leadership is not caused by gender but through the means of democratic and constitutional leadership, as well as the protection of human rights, not tyrannical, authoritarian and centralistic power. Therefore, the Quranic verses and the hadith of the prophet that are "already" understood as the basis for subordinated women must be re-understood through cultural and social perspectives. Because, historical facts show some women who were brilliantly successful in leading their people, on the contrary, it was also found the failure of men in leading their people.